An Economic Sociological Look at Relationship Marketing - Zoya Kotelnikova (Journal of Economic Sociology, 2014)
The paper reviews the state-of-the-art in relationship marketing and new economic sociology. The author pays attention to the closeness of both perspectives which have common roots (Durkheimian sociology, economic anthropology, sociology of law, social exchange theory) and common research interests (trust, commitment, interdependency, shared values, power asymmetry, adaptation, and mutual contentment). Despite the intersections, relationship marketing and new economic sociology appear to have been developing in parallel worlds, implying that these disciplines remain disconnected and persistently ignore each other’s accomplishments.This is conditioned by several reasons. Firstly, economic sociologists are inspired by the investigation of peculiar and peripheral types of markets, while marketing scholars usually study the“standard markets”. Secondly, relationship marketing defines its subject matter as exchange relationships per se. In contrast with relationship marketing, new economic sociology has a much wider scope of interests. Thirdly, relationship marketing focuses on ongoing relationships while new economic sociology concentrates on relations that are beyond the market exchange per se. Finally, marketing scholars typically prioritize formal contractual relationships, whereas economic sociologists devote more attention to informal, interpersonal relationships. The author comes to the conclusion that, if specialists in relationship marketing and new economic sociologists could overcome the divide, their perspectives would benefit greatly, specifically in developing their market theories.